2022
DOI: 10.1371/journal.pone.0263912
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and disease burden of androgenetic alopecia in college freshmen in China: A population-based study

Abstract: Objective To evaluate the epidemiology and disease burden of androgenetic alopecia (AGA) in college freshmen in China. Methods This population-based cross-sectional survey was carried out among 9227 freshmen of two comprehensive universities in two cities of China (Changsha and Xiamen) from September 2018 to October 2018. Questionnaires covering basic issues, surrounding demographic information, history of diseases, living habits, comorbidities, etc. were completed online in a self-reported manner Dermatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The mean age of study participants was 40.5 ± 13.7 years, which supports the current view that the risk of androgenic alopecia is linked with older individuals (Lolli et al, 2017). Moreover, the gender representation in this study also supports the current epidemiology of the disease, with males representing two-thirds of affected individuals in this study (He et al, 2022). In addition, previous studies have reported a milder degree of hair loss in females compared to males owing to the different pathophysiology of the disease among males and females (Price et al, 2003;Redleret al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…The mean age of study participants was 40.5 ± 13.7 years, which supports the current view that the risk of androgenic alopecia is linked with older individuals (Lolli et al, 2017). Moreover, the gender representation in this study also supports the current epidemiology of the disease, with males representing two-thirds of affected individuals in this study (He et al, 2022). In addition, previous studies have reported a milder degree of hair loss in females compared to males owing to the different pathophysiology of the disease among males and females (Price et al, 2003;Redleret al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Its incidence is increasing year by year and it is appearing in younger individuals [2]. Although AGA does not cause direct harm to the body, it may bring serious psychological pressure to patients, resulting in negative emotions such as inferiority, anxiety and depression and seriously affecting personal social activities and quality of life [3]. Therefore, treating hair loss is necessary to maintain the physical and mental health of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The most common age of onset remains to be the third and fourth decades of life. It is a disease of progressive nature 1,2,3 . Males have been reported to be affected almost four times higher as compared to females according to an Indian study 4 .…”
Section: Introductionmentioning
confidence: 99%